Mannose Binding Lectin, S100 B Protein, and Brain Injuries in Neonates With Perinatal Asphyxia - Auriti, Cinzia; Prencipe, Giusi; Inglese, Rita; Moriondo, Maria; Nieddu, Francesco; Mondı̀, Vito; Longo, Daniela; Bucci, Silvia; Del Pinto, Tamara; Timelli, Laura; Di Ciommo, Vincenzo Maria (Frontiers in Pediatrics, 2020)
Perinatal asphyxia triggers an acute inflammatory response in the injured brain. Complement activation and neuroinflammation worsen brain damage after a systemic ischemia/reperfusion insult. The increase of mannose binding lectin (MBL) during asphyxia may contribute to the brain damage, via activation of the complement lectin pathway. The possible role of MBL2 gene variants in influencing the severity of post-asphyxia brain injuries is still unexplored. This retrospective study included 53 asphyxiated neonates: 42 underwent therapeutic hypothermia (TH) and 11 did not because they were admitted to the NICU later than six hours after the hypoxic insult. Blood samples from TH-treated and untreated patients were genotyped for MBL2 gene variants and biomarker plasma levels (MBL and S100 B protein) were measured at different timepoints: during hypothermia, during re warming and at 7–10 days of life. The timing of blood sampling, except for the T1 sample, was the same in untreated infants. Highest (peak) levels of MBL and MBL2 genotypes were correlated to neuroimaging brain damage or death and long-term neurodevelopmental delay. MBL2 wild-type genotype was associated with the highest MBL levels and worst brain damage on MRI (p=0.046) at 7–10 days after hypoxia. MBL increased in both groups and S100B decreased, slightly more in treated than untreated neonates. The progressive increase of MBL (p=0.08) and to be untreated with TH (p=0.08) increased the risk of brain damage or death at 7–10 days of life, without affecting neurodevelopmental outcomes at one year. The effect of TH on MBL plasma profiles is uncertain.